Evaluation of genetic polymorphisms at 21 autosomal STR loci in Ramgharia Sikh population of Punjab, India. (18th August 2022) - Bhambara, Amandeep Kaur; Singh, Abhishek; Sahajpal, Vivek; Thakur, Mukesh; Bhandari, Deepika; Sharma, Shivkant; Thakar, Mukesh Kumar
Abstract: Background: STR (Short Tandem Repeat) markers are highly polymorphic markers, which are widely used in forensics DNA analysis and aid to ascertain unique genotype profiles of individuals and determine the genetic diversity of the given population. Aim: In the present study, an attempt has been made to evaluate the population genetic diversity of the Ramgharia Sikh population of Punjab, India, using 21 autosomal STR loci (D3S1358, vWA, D16S539, CSF1PO, TPOX, D8S1179, D21S11, D18S51, D2S441, D19S433, TH01, FGA, D22S1045, D5S818, D13S317, D7S820, SE33, D10S1248, D1S1656, D12S391, and D2S1338) to augment the emerging forensic database related to the indigenous population of India. Subjects and methods: For generation of the database, 200 (blood on FTA card) samples were obtained from genetically unrelated Ramgharia Sikhs residing in the state of Punjab. Twenty-one autosomal STR markers were analysed using the Globalfiler ® PCR amplification kit. Results: With the help of various statistical tools, a total of 232 alleles were observed and 11.048 ± 1.284 (mean ± standard deviation) alleles per locus were recorded. No locus deviated from Hardy Weinberg Equilibrium. SE33 locus was found to be the most polymorphic and exhibited the highest discrimination power, that is, 0.99. Moreover, results further indicated that Ramgharia Sikhs of Punjab showed a high affinity with Bhils of Madhya Pradesh (India). Thus, the studied population showed genetic proximity with the geographically close populations of India and showed significant genetic variations with distant populations, which was evident from the UPGMA tree and Principal Component Analysis plot. Conclusion: Overall, the 21 autosomal STRs were found to be polymorphic in the Ramgharia population and suitable for forensic casework and studies on population genetics.